Quantum CNOT Gate Operation using Dark-Bright Soliton Pair - Suphanchai Punthawanunt; Preecha P. Yupapin; Xaythavy Louangvilay; Somsak Mitatha (My University, 2011)
A simple system of a quantum CNOT gate operation using dark and bright solitons in a Mach Zhender interferometer (MZI) is proposed. In this concept, two qubits are randomly generated by using the coincidence dark and bright soliton states within the MZI, in which (D ) and (B ) represent the orthogonal dark and bright soliton states, which they are input into the MZI input ports simultaneously. The randomly input dark and bright soliton pulses can perform the random logical codes after propagating through a phase retarder of (π/2). By using low power soliton, the soliton power can reduce to a single photon power (10-6 W), where finally the quantum gate can be performed by using the single photon detection scheme. The quantum controlled-NOT (CNOT) gate is formed by controlling the input and coincidence solitons (photons), where in some cases the phase shifter is required to obtain the coincidence solitons. type your own text. This preparation guide is a slight modification of IEEE format.
Keywords: Controlled NOT gate; Quantum Information and Cryptography